Menelusuri Peran Strategis Kecerdasan Emosional dalam Meningkatkan Prestasi Akademik Mahasiswa: Kajian Psikopedagogis terhadap Interaksi Emosi, Motivasi, dan Lingkungan Belajar (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to explore the strategic role of emotional intelligence in enhancing students’ academic achievement through a psychopedagogical approach that emphasizes the interaction between emotions, motivation, and learning environments. Employing a literature review method with a qualitative approach and descriptive analysis, the data were collected from 50 scholarly articles published between 1979 and 2025 on the Google Scholar platform. After a rigorous selection process, 22 articles were deemed relevant to the research focus. Data collection was carried out using keywords aligned with the topic, and data analysis was conducted descriptively by identifying, categorizing, and synthesizing findings across the selected articles. The results indicate that emotional intelligence—which includes the ability to recognize, understand, and manage one’s own emotions and those of others—significantly contributes to increased intrinsic motivation, academic engagement, and students’ adaptability within learning environments. These findings are supported by emotional intelligence theories from Mayer and Salovey as well as Goleman, the Self-Determination Theory of motivation, and Bronfenbrenner’s ecological theory of learning.